Les Hors nature et La Jongleuse de Rachilde : entre le réalisme du « donner à voir » et la représentation de l’impossible - Staroń, Anita (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2018)
The style of Rachilde which abounds in picturesque comparison invites a reader to examine her use of hypotyposis. Two of her novels: Les Hors Nature and La Jongleuse offer particularly interesting examples of this figure, both of them mainly in erotically uninhibited scenes. Because of the bowdlerisation of the time, while impressing the reader's imagination with the power of images, Rachilde had to avoid clear wording and resort to suggestion. That’s why many rhetorical figures: ellipses, circumlocutions, metaphors blur the clarity of description, which according to Yves Le Bozec makes one of the formal features of hypotypose. The aim of this paper is to analyse the construction of this figure in Rachilde's literary output. — On the other hand, the scenes in question were designed to illustrate the concept of ideal love – the impossible one – that the novelist develops in her works. Crossing the limits of the theoretical discourse, the protagonists direct their own performances, watched by the stunned and outraged viewers. This way of presentation enhances the hypotypotique effect. The reactions of eyewitnesses replace the phrases designed to encourage the audience to observe the scene. Such phrases are common in theatrical hypotyposis. This interweaving is designed to impress the reader deeply. — However, the question arises whether Rachilde, despite her primary axiological intention, did not succumb to the temptation to provoke the public with shocking images, and whether the strength of her hypotyposis does not remain, in the end, one of her major achievements.